Variable Genotype–Phenotype Correlation of Pompe's Disease Caused by a c.2015 G > A (p.Arg672Gln) Mutation in the GAA Gene - Tokatly Latzer, Itay; Sagi, Liora; Bali, Deeksha Sarihyan; Rehder, Catherine; Orbach, Rotem; Fattal-Valevski, Aviva (Neuropediatrics, 2021)
Pompe's disease occurs due to an autosomal recessive trait resulting from numerous distinctive mutations in the GAA gene. It manifests as a broad spectrum of clinical phenotypes with progressive weakness that impairs motor and respiratory functions being common for all its forms. Cardiac hypertrophy is a prominent feature of its classic infantile form. To date, the pathogenic variant c.2015G > A (p.Arg672Gln) in exon 14 of the GAA gene has been described in 10 children of different ethnic groups, with variable phenotypic presentations. This work describes three children from two unrelated families of Arab ethnicity who presented with infantile-onset Pompe's disease as a result of a c.2015G > A (p.Arg672Gln) mutation. The clinical course of the children we report was more severe than previous reports. This further emphasizes the lack of a strict genotype–phenotype correlation in regard to the unique c.2015G > A (p.R672Q) mutation that causes Pompe's disease. This information contributes to the knowledge of the phenotypic expression of the specific mutation c.2015G > A (p.Arg672Gln) that causes Pompe's disease.
Keywords: Pompe's disease; genetic; genotype–phenotype; mutation; variant; children